(untitled) (Bangladesh Journal of Botany, 2023)
Diurnal variations of photosynthesis and leaf anatomical structure characteristics of Cornus walteri seedlings under three light conditions, including L0 (under full light radiation), L1 (under natural tree shade), L2 (under one layer of shading) were studied. Results showed that, Pn under different light regimes showed asymmetric convex linear changes. The variation of Pn under L0 was the strongest; the maximum of Pn appeared at 12:00 AM, that of Gs was so. Photosynthetic Active Radiation (PAR) under L2 was insufficient, so Pn decreased significantly, and the peak was at 10:00 AM. Pn and Gs under L1 changed gently.The daily average sequence of Pn was L0＞L2＞L1 and Ci showed the reverse sequence. Shading had a significant effect on photosynthetic response parameters of Cornus walteri seedlings, which caused a significant decrease of LCP, LSP, and decline of Pnmax，AQY and Rd was so. Under shading, leaves of Cornus walteri seedlings became thinner, thickness of epidermal cells (EP) decreased significantly, thickness of both PT and ST reduced. Cornus walteri was intolerant tree species, which has certain physiological regulation ability to weak light, but severe shading will hinder seedling growing. So it was suggested to raise seedlings under full light, and create a favorable condition for seedlings growing. Bangladesh J. Bot. 52(2): 395-402, 2023 (June)